Recognising and responding to suicidal crisis within family and social networks: qualitative study - Owens, Christabel (BMJ Publishing Group Ltd., 2011)
Objective To shed light on the difficulties faced by relatives, friends, and colleagues in interpreting signs of suicidality and deciding whether and how to intervene. Design Qualitative study of completed suicides, based on in-depth interviews with multiple informants. Setting London, southwest England, and south Wales. Participants 31 lay informants (one to five for each case), including parents, partners, siblings, friends, and colleagues of 14 cases of suicide in which the deceased was aged 18-34 and was not in contact with secondary mental health services. Results Informants described both intellectual and emotional barriers to awareness and intervention within the family and social network. They reported that signs and communications of distress were often oblique and difficult to interpret, that they may have disregarded warning signals and focused instead on positive signs, and that, even when they were aware that something was seriously wrong, taking any action at all involved considerable personal risks. Conclusions As the suicidal process unfolds, significant others are faced with a highly complex task. Their proximity to the suicidal person and their emotional investment in the relationship make it difficult for them to see what is happening, to say anything to the person or to other members of the network, or to seek help outside the network. Efforts to strengthen the capacity of lay people to play a role in preventing suicide are urgently needed and should be informed by a thorough understanding of these difficulties. They should highlight the ambiguous nature of warning signs and should focus on helping people to acknowledge and overcome their fears about intervening.